2009
DOI: 10.1164/rccm.200809-1486oc
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of a New Tuberculosis Vaccine, MVA85A, in Mycobacterium tuberculosis–infected Individuals

Abstract: Rationale: An effective new tuberculosis (TB) vaccine regimen must be safe in individuals with latent TB infection (LTBI) and is a priority for global health care. Objectives: To evaluate the safety and immunogenicity of a leading new TB vaccine, recombinant Modified Vaccinia Ankara expressing Antigen 85A (MVA85A) in individuals with LTBI.Methods: An open-label, phase I trial of MVA85A was performed in 12 subjects with LTBI recruited from TB contact clinics in Oxford and London or by poster advertisements in O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
82
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 55 publications
12
82
2
2
Order By: Relevance
“…These data thus provide compelling evidence of M72/AS01-mediated boosting of discrete T-cell populations primed by natural Mtb infection; moreover, they suggest that M72/AS01 may induce functionally distinct profiles of M72-specific T cells in Mtbinfected versus -uninfected individuals. These findings contrast with previously reported observations in a small clinical trial of adults vaccinated with MVA85A, in which no differences were found in the magnitude of Ag85A-specific IFN-g-producing T cells between Mtb-infected and BCG-vaccinated, Mtbuninfected participants after vaccination (39).…”
Section: Discussioncontrasting
confidence: 99%
“…These data thus provide compelling evidence of M72/AS01-mediated boosting of discrete T-cell populations primed by natural Mtb infection; moreover, they suggest that M72/AS01 may induce functionally distinct profiles of M72-specific T cells in Mtbinfected versus -uninfected individuals. These findings contrast with previously reported observations in a small clinical trial of adults vaccinated with MVA85A, in which no differences were found in the magnitude of Ag85A-specific IFN-g-producing T cells between Mtb-infected and BCG-vaccinated, Mtbuninfected participants after vaccination (39).…”
Section: Discussioncontrasting
confidence: 99%
“…A role for CD8 ϩ T cells in the protection against TB has been demonstrated (15,23,27,32). Similar to results from an earlier study with Mtb72F/AS02 A (42) and studies with the MVA85a TB vaccine candidate (5,18,31), no vaccine-induced antigen-specific CD8 ϩ T cells could be detected by ICS using a short-term in vitro restimulation.…”
Section: Discussionsupporting
confidence: 78%
“…This is the first study which demonstrates the polyfunctionality of vaccine-induced CD4 ϩ T cells in PPD-negative subjects. Other studies of TB vaccine candidates have demonstrated polyfunctional CD4 ϩ T-cell responses in PPD-positive adults (2,5,18,31). Earlier work showed that the MVA85a TB vaccine candidate was immunogenic in PPD-negative British adults and that the magnitude of the IFN-␥ enzyme-linked immunospot assay response was positively influenced by BCG priming (26).…”
Section: Discussionmentioning
confidence: 99%
“…In general, these subunit candidates are intended to enhance preexisting immune responses to certain immunodominant antigens induced upon BCG vaccination at birth and or upon M. tuberculosis infection in BCG vaccinated individuals (infants, e.g. MVA85A vaccine trial in adolescents and adults) [35][36][37].…”
Section: The Current Clinical Tb Vaccine Pipelinementioning
confidence: 99%